Control of Green Apple Aphid (Aphis pomi De Geer) in Organic Apple Production (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The efficacy of methods used to control populations of green apple aphid (Aphis pomi De Geer) in organic apple orchards was compared over three consecutive years. The following three control methods were tested: a) predator activity (Coccinela septempunctata), b) predator activity (C. septempunctata) + selective spraying of trees on which infestation level exceeded 10% with a botanical insecticide (NeemAzal T/S), and c) predator activity (C. septempunctata) + total spraying of all trees in orchard with the botanical insecticide (NeemAzal T/S). In terms of maintaining a biological balance within orchard, the combination of natural regulation by C. septempunctata and selective spraying of individual trees with NeemAzal T/S proved to be the most efficient method.
Keywords: Azadirachtin; Coccinella septempunctata; Organic agriculture; Botanical insecticides; Spraying; Predators; Apples; Aphis pomi